Karakteristik Emisi CO dan HC Mesin bensin SOHC 110cc Berbahan bakar Pertalite-Alkohol - Syarifudin; Fatkhurrozak, Faqih; Lukman Sanjaya, Firman; Yohana, Eflita; Syaiful (Infotekmesin, 2022)
Community economic activities that encourage motorized vehicles are getting higher. This exacerbates dependence on fossil fuels and air pollution. The outside air that is contaminated with exhaust gases from combustion products is very dangerous for human health. Motorized vehicles such as motorcycles are the largest cause of air pollution. Alcohols have high octane number and low viscosity. The use of ethanol and methanol alcohols is very diverse, so they are easy to obtain. Therefore, alcohol ethanol and methanol are suitable as premium fossil fuel mixtures. This study aims to observe the CO and HC emission characteristics of the gasoline engine using a premium-alcohol mixture of ethanol, methanol. The alcohol concentration was varied from 5% to 15% at 5% intervals. The petrol engine is operated at 2000, 3000, and 4000rpm. Commercial Gas Analyzers are used to measure CO and HC emissions coming out of the exhaust. The results of the observations present the CO and HC emissions of the engine with premium-ethanol fuel, methanol is lower than pure premium (P100). CO emissions from PE15 fuel decreased to 66,30%, and PM15 decreased to 90,63%. Meanwhile, PE15 fuel HC emissions decreased by 58,94%, and PM15 decreased by 68,60%.